If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7t + 5) + -1(3t + -5) = 0 Reorder the terms: (5 + 7t) + -1(3t + -5) = 0 Remove parenthesis around (5 + 7t) 5 + 7t + -1(3t + -5) = 0 Reorder the terms: 5 + 7t + -1(-5 + 3t) = 0 5 + 7t + (-5 * -1 + 3t * -1) = 0 5 + 7t + (5 + -3t) = 0 Reorder the terms: 5 + 5 + 7t + -3t = 0 Combine like terms: 5 + 5 = 10 10 + 7t + -3t = 0 Combine like terms: 7t + -3t = 4t 10 + 4t = 0 Solving 10 + 4t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 4t = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 4t = 0 + -10 4t = 0 + -10 Combine like terms: 0 + -10 = -10 4t = -10 Divide each side by '4'. t = -2.5 Simplifying t = -2.5
| 3x+3y+4=x+2y+1 | | 4x-8=-2x-5 | | (x-6)(x+6)=(x-6)(x-6) | | (x-6)(x+6)=(x-6)x(x-6) | | y-5.9=7.22 | | 8x+18=30 | | 2x^4y^2z^2= | | 0=9x+0.25y | | 3Xsquare-13X-10=0 | | 3y^2-11y-30=0 | | 4+25=100 | | 2(3z+3)=(2+1)(3-5) | | 5f+20-6f-30= | | X-3y=36 | | 20=12((5-x)+x+(4-x))+10-((5-x)+x+(6-x))+11-((4-x)+x+(6-x)) | | 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) | | 9x-5x-8=360 | | 7x-13-x=5 | | x=5x-25 | | 9x-5x-8= | | 5x+25=7x+50 | | -20z+28=25-16z-12+2z-6z | | y=x^2+m-4x | | 3*2+2=7*2-6 | | 2p+3-3p+8= | | a^2-6a+6=0 | | a^2-8a+b^2-2b+17=0 | | 9a^2-6a+b^2-2b+2=0 | | 35=-10+2x | | 3.7x=0.4 | | (12x^2)+(5x^2)+4x= | | 51+14x=x |